TRPM4 Blocking Antibody Protects Cerebral Vasculature in Delayed Stroke Reperfusion - Bo Chen; Shunhui Wei; See Wee Low; Charlene Priscilla Poore; Andy Thiam-Huat Lee; Bernd Nilius; Ping Liao (Biomedicines, 2023)
Reperfusion therapy for acute ischemic stroke aims to restore the blood flow of occluded blood vessels. However, successful recanalization is often associated with disruption of the blood-brain barrier, leading to reperfusion injury. Delayed recanalization increases the risk of severe reperfusion injury, including severe cerebral edema and hemorrhagic transformation. The TRPM4-blocking antibody M4P has been shown to alleviate reperfusion injury and improve functional outcomes in animal models of early stroke reperfusion. In this study, we examined the role of M4P in a clinically relevant rat model of delayed stroke reperfusion in which the left middle cerebral artery was occluded for 7 h. To mimic the clinical scenario, M4P or control IgG was administered 1 h before recanalization. Immunostaining showed that M4P treatment improved vascular morphology after stroke. Evans blue extravasation demonstrated attenuated vascular leakage following M4P treatment. With better vascular integrity, cerebral perfusion was improved, leading to a reduction of infarct volume and animal mortality rate. Functional outcome was evaluated by the Rotarod test. As more animals with severe injuries died during the test in the control IgG group, we observed no difference in functional outcomes in the surviving animals. In conclusion, we identified the potential of TRPM4 blocking antibody M4P to ameliorate vascular injury during delayed stroke reperfusion. If combined with reperfusion therapy, M4P has the potential to improve current stroke management.